Pendampingan Pelatihan Model Pembelajaran Quantum Teaching pada Tenaga Pendidik - Abdurahman, Ayi; Setiawati, Setiawati; Christine, Sri Erwini (LP2M INSURI Ponorogo, 2023)
The quality of education depends on the quality of the learning process, for this reason an appropriate learning model is needed. This study aims to overcome the problem of low student scores caused by the lack of effectiveness of the learning methods used. As an alternative option, the quantum teaching learning model can be applied to improve student learning outcomes. The research approach applied is a quantitative experimental design using the ABCD (Audience, Behavior, Conditions, and Degree) training model. Data collection methods used include observation, communication, document study, and measurement techniques. The tools used to collect data included observation guides/checklists, interview guides, questionnaires, documentation, and tests. Data analysis was carried out by testing for normality and conducting a paired samples test. Based on the research results in the